EKSPERIMENTASI MODEL PROJECT BASED LEARNING (PjBL) DAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) PADA MATERI POKOK BANGUN RUANG DITINJAU DARI KECERDASAN EMOSIONAL SISWA KELAS VIII SMP NEGERI SE-KOTA METRO LAMPUNG - Mustika, Juitaning; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Universitas Sebelas Maret, 2015)
Abstract: The objective of research was to investigate the effect of learning models on Mathematics learning achievements viewed from students’ emotional intelligence. The learning models compared were PjBL, GI and direct learning model. This study was a quasi experimental research with a 3 x 3 factorial design. The population of research was all of the VIII graders of Junior High Schools in Metro City. The sample was taken using stratified cluster random sampling. The sample of research consisted of 238 students with details 80 students for the experiment 1, 80 students for experiment 2 and 78 students for control classes. The instruments used for collecting data were mathematics learning achievement test and student EI questionnaires. The results of this research were as follows: (1) the use of the PjBL model couldresult better learning achievement than both GIandthe direct learning. The use of GI could result better learning achievement than the direct learning model, (2) Students with high EI, resulting better learning achievement than students with moderate or low EI, and students with moderate EI hadbetter learning achievement than students with low EI, (3) For those students with high and moderate EI, the PjBL modelresulted better learning achievement than direct learning model, while the PjBL models gave the same learning achievement asGI, and the GIgavethe same learning achievement as the direct learning model. For students with low EI, PjBL, GIand direct learning model gave the same learning achievement, (4) In learning using PjBL model, students with high EI had better learning achievement than students with low EI, and students with moderate EI had better learning achievement than students with low EI, while students with high EI had the same learning achievement as students with moderate EI. On learning using GImodel, students with a high EI had better learning achievement than thosewith low EI, while students with high EI had the same learning achievement as students with moderate EI and students with moderate EI had the same learning achievement as students with a low EI. Direct learning model gave the same effect on learning outcomes among students who had high, moderate and low EI.Keywords: Project Based Learning (PjBL), Group Investigation (GI), Direct learning andEmotional Intelligence (EI).